Modelling the Jamaican business cycle : a structural vector autoregressive approach - Murray, André (Bank of Jamaica [Kingston]JM, 2007)
Develops an open economy structural vector autoregressive (SVAR) model of the Jamaican economy. Seeks to identify and disaggregate the main factors that drive the Jamaican business cycle. Provides an additional mechanism for the examination of the transmission of monetary policy to effect changes to prices in this small open island state.